The Genetic Relationship Between Balinese and Madurese - Ni Putu Parmini; I Wayan Mawa; I Wayan Soper; I Made Suparta; Ni Made Sueni; I Gede Bagus Wisnu Bayu Temaja (International Journal of Education, Vocational and Social Science, 2024)
This study aimed to identify the genetic relationship between Balinese and Madurese through historical linguistics study. The results show that the percentage of genetic relationships in both languages is 47% and was presumed to diverge around 278 - 443 AD (as in 2018). Qualitatively, there are fifteen sets of sound correspondences, i.e., / a - e /, / i - e /, / ə - a /, / a - ə /, / ə - e /, / u - o /, / ∅ - Ɂ /, / k - Ɂ /, / h - r /, / t - Ɂ /, / h - ∅ /, / b - bh /, / g - gh /, / d - dh /, and / j - jh /. Balinese maintained 23 proto lexicons in Proto-Austronesian lexicons (12%), a retention more than Madurese’s five lexicons (2.5%).